Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/mc.22670
|View full text |Cite
|
Sign up to set email alerts
|

Apurinic/apyrimidinic endonuclease 1 (APE1/Ref‐1) overexpression is an independent prognostic marker in prostate cancer without TMPRSS2:ERG fusion

Abstract: Polymorphisms of the base excision repair gene APE1 may be associated with an increased risk for developing prostate cancer. In other cancer types, altered APE1 protein expression is a candidate prognostic marker. Using immunohistochemistry, we thus analyzed APE1 expression in 9763 prostate cancers in a tissue microarray (TMA) with attached clinical and molecular data. The comparison with normal prostate tissue revealed an upregulation of APE1 in cancer samples. APE1 immunostaining was considered weak in 20.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…Consistently, we showed that the non‐chemosensitive group has a significantly higher level of abnormal expression of APE1/Ref‐1 protein than the chemosensitive group, suggesting that a defective DNA BER mechanism may be one of the important chemoresistance mechanisms in HGSC. And consistent with our observation, several literatures reported that dysregulated APE1/Ref‐1 protein expression also predicts a poor prognosis in prostate cancer and ovarian cancer .…”
Section: Discussionsupporting
confidence: 92%
“…Consistently, we showed that the non‐chemosensitive group has a significantly higher level of abnormal expression of APE1/Ref‐1 protein than the chemosensitive group, suggesting that a defective DNA BER mechanism may be one of the important chemoresistance mechanisms in HGSC. And consistent with our observation, several literatures reported that dysregulated APE1/Ref‐1 protein expression also predicts a poor prognosis in prostate cancer and ovarian cancer .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we compared the expression of PSCA with molecular attributes associated with genomic instability, chromosomal deletion and tumor cell proliferation [ 37 ]. We found previously that features with a role in cell cycle control (p16 [ 39 ] or APE1 [ 40 ]) were significantly associated with a high Ki67 labeling index. Molecular attributes linked to genomic instability (MSH6/PMS2/MLH1 [ 41 ], ELAV1 [ 42 ], or HOOK3 [ 43 ]) were found to be associated with chromosomal deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its involvement in essential cellular processes such as genome stability and gene expression regulation, the importance of APE1 in human pathologies such as cancers, neurological diseases, and age-associated disorders is not surprising. Many studies have shown that APE1 is overexpressed in a variety of cancers, suggesting a possible prognostic significance and therapeutic target for this protein [ 26 29 ]. Data from different laboratories support a correlation between the increased expression levels of APE1 and HCC progression [ 30 33 ] and uphold the hypothesis that APE1 loss of expression suppresses proliferation and migration [ 34 – 36 ].…”
Section: Introductionmentioning
confidence: 99%